Depth, Polarity and Welding Current Effect on Diffusible Hydrogen Content With Stainless Steel Electrodes in Underwater Wet Welding (2022)
The evaluation of diffusible hydrogen is critical in determining the quality and strength of UnderWater Wet Welding joints. The objective of this study was to separately evaluate the influence of four fundamental variables on the amount of diffusible hydrogen in underwater welding: welding depth, polarity, current and electrode specification. Applying a full two-level factorial design to these four factors. Statistical analysis allowed us to establish the relevance of the variation of each factor on the diffusible hydrogen content of the welds. Austenitic stainless steel electrodes were used. The lowest Diffusible Hydrogen values were obtained at higher depth and welding current levels, with positive polarity, and electrode E312 in detriment to E309. In this study, the factorl with the greatest impact on Diffusible Hydrogen was the Welding Depth.